2017
DOI: 10.1016/j.actbio.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Solution blow spinning fibres: New immunologically inert substrates for the analysis of cell adhesion and motility

Abstract: The control of cell behaviour through material geometry is appealing as it avoids the requirement for complex chemical surface modifications. Significant advances in new technologies have been made to the development of polymeric biomaterials with controlled geometry and physico-chemical properties. Solution blow spinning technique has the advantage of ease of use allowing the production of nano or microfibres and the direct fibre deposition on any surface in situ. Yet, in spite of these advantages, very littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 64 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…B16F1 cells (ATCC CRL 6323) and B16F1 cells stably expressing RFP-zyxin [ 10 , 50 ] were grown in DMEM high glucose supplemented with 10% FCS, 2 mM L-glutamine, 1 mM sodium pyruvate, 100 μg mL -1 streptomycin and 100 U mL -1 penicillin at 37°C, 5% CO 2 . Control and Gas2L1 knock out Sertoli cells were grown in DMEM/F12 [1:1] supplemented with 10% FCS, 2 mM L-glutamine, 100 μg mL -1 streptomycin and 100 U mL -1 penicillin at 37°C, 5% CO 2 [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B16F1 cells (ATCC CRL 6323) and B16F1 cells stably expressing RFP-zyxin [ 10 , 50 ] were grown in DMEM high glucose supplemented with 10% FCS, 2 mM L-glutamine, 1 mM sodium pyruvate, 100 μg mL -1 streptomycin and 100 U mL -1 penicillin at 37°C, 5% CO 2 . Control and Gas2L1 knock out Sertoli cells were grown in DMEM/F12 [1:1] supplemented with 10% FCS, 2 mM L-glutamine, 100 μg mL -1 streptomycin and 100 U mL -1 penicillin at 37°C, 5% CO 2 [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed and permeabilised as described earlier [ 10 , 50 , 57 ]. Briefly, the actin cytoskeleton was labelled with Alexa 594-conjugated phalloidin (0.3 U mL -1 , cat.…”
Section: Methodsmentioning
confidence: 99%
“…The fibers produced by solution blow spinning have some similar characteristics to fibers obtained by other techniques (electrospinning, gas jet spinning, nozzle‐free centrifugal spinning, rotary jet spinning, and flash‐spinning) . However, this technology have some advantages, such as high production rate, the possibility of in situ application, low construction cost of the spinning system, and application in any substrate, among others …”
Section: Introductionmentioning
confidence: 94%
“…Polylactic acid has good biocompatibility, biodegradability (degradation product is non-toxic lactic acid), and mechanical properties. It is a biomaterial approved by the US Food and Drug Administration for in-vivo transplantation and thus becomes one of the most commonly used electrospun synthetic polymer materials for soft tissue repair (Paschoalin et al, 2017 ). However, the simple surface of the PLA molecule is highly hydrophobic and lacks a cell recognition site, which is not conducive to the rapid adhesion, migration, and regeneration of tissue cells.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, PLA and gelatin composites have advantages of both materials, which cannot only maintain the mechanical properties but also delay the degradation rate so that it matches the speed of tissue repair and regeneration. The electrospun nanofibers of polymer materials have good properties, such as porosity, water retention, tissue compatibility, and mechanical properties, and are, therefore, favored in the field of tissue repair, including skin, dura mater, muscle, bone, and cartilage (Su and Wang, 2015 ; Paschoalin et al, 2017 ; Zarei and Soleimaninejad, 2018 ). It has been reported that electrospun nanofibers of PLA/gelatin blends are one of the most ideal material combinations for soft tissue repair applications (Liu et al, 2014 ; Xu et al, 2015 , 2017 ; Deng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%